Clubs of autocrats: Regional organizations and authoritarian survival - Maria J. Debre (The Review of International Organizations, 2021)
While scholars have argued that membership in Regional Organizations (ROs) can increase the likelihood of democratization, we see many autocratic regimes surviving in power albeit being members of several ROs. This article~argues that this is the case because these regimes are often members in "Clubs of Autocrats" that supply material and ideational resources to strengthen domestic survival politics and shield members from external interference during moments of political turmoil. The~argument is supported by survival analysis testing the effect of membership in autocratic ROs on regime survival between 1946 to 2010. It finds that membership in ROs composed of more autocratic member states does in fact raise the likelihood of regime survival by protecting incumbents against democratic challenges such as civil unrest or political dissent. However, autocratic RO membership does not help to prevent regime breakdown due to autocratic challenges like military coups, potentially because these types of threats are less likely to diffuse to other member states. The article thereby adds to our understanding of the limits of democratization and potential reverse effects of international cooperation, and contributes to the literature addressing interdependences of international and domestic politics in autocratic regimes.
Keywords: 320; Regional organizations; Authoritarian resilience; Democratization; Survival analysis; Domestic politics